Pengaruh Current Ratio, Debt to Equity Ratio, Return on Assets, Growth dan Firm Size terhadap Kebijakan Dividen: Studi pada Perusahaan yang Tercatat Aktif di BEI yang Membagikan Dividen Periode 2012-2015: Kata Kunci: Current Ratio (CR), Debt to Equity Ratio (DER), Return On Assets (ROA), Growth, Firm Size, and Dividen Payout Ratio (DPR) - Mikael Abraham Deswanto Prabowo; Clara Alverina (Universitas Kristen Maranatha, 2020)
This paper aims to determine the effect of liquidity, solvency, profitability, growth and firm size on the dividend payout ratio. Population and sample are companies that routinely distribute dividends that are listed on the Indonesia Stock Exchange website during the period of 2012 to 2015. To obtain valid research results, the sampling technique used in this study was using purposive sampling technique. The method of analysis is done by using classical testing on five independent variables then F test and t test.